Sea-ice growth and water mass modification in the Mertz Glacier Polynya, East Antarctica, during winter - Nathaniel Bindoff; Guy Williams; Ian Allison (2001)
In July-September 1999, an extensive oceanographic survey (87 conductivity-, temperature- and depth-measuring stations) was conducted in the Mertz Glacier polynya over the Adélie Depression off the Antarctic coast between 145° and 150° E. We identify and describe four key water masses in this polynya: highly modified circumpolar deep water (HMCDW), winter water (WW), ice-shelf water (ISW) and high-salinity shelf water (HSSW). Combining surface velocity data (from an acoustic Doppler current-profiler) with three hydrographic sections, we found the HMCDW to be flowing westward along the shelf break (0.7 Sv), the WW and HSSW flowing eastwards underneath Mertz Glacier (2.0 Sv) and that there was a westward return flow of ISW against the continent (1.2 Sv). Using a simple box model for the exchanges of heat and fresh water between the principal water masses, we find that the polynya was primarily a latent-heat polynya with 95% of the total heat flux caused by sea-ice formation. This heat flux results from a fresh-water-equivalent sea-ice growth rate of 4.9-7.7 cm d1 and a mass exchange between HMCDW and WW of 1.45 Sv The inferred ocean heat flux is 8-14 W m2 and compares well with other indirect estimates.